Design and synthesis of rotational analogues of estradiol - Seymour, Anthony James (Department of Chemistry, 2024)
Studies have been conducted in synthesising bridged analogues of estradiol in which the ring D hydroxy group is displaced from the 17-position. The aim was to explore the possible rotational equivalence between such analogues and estr~diol. The synthetic routes investigated were based upon cycloaddition to 3-methoxyestra1,3,5(10), 14, 16-pentaene. In the first phase of the project, two approaches for the synthesis of this diene were explored. The first entailed the vinylogous Shapiro elimination of the tosylhydrazone of 3-methoxyestra-1,3,5(10),15-tetraen-17-one to give the 14,16-diene. The second involved conversion of 3-methoxyestra1,3,5(10), 15-tetraen-17-one into the corresponding dienyl triflate, followed by palladium(0) mediated deoxygenation to afford the 14, 16-diene. Of these two methods, only the latter was successful, as the tosylhydrazone of 3-methoxyestra1,3,5(10), 15-tetraen-17-one could not be synthesised. In the second phase of the work~ cycloaddition of 2-chloroacrylonitrile to the 14,16- diene, followed by alkaline hydrolysis afforded 3-methoxy-14, 17a.-ethenoestra- , 1,3,5(10)-trien-15-one and 3-methoxy-14, l 7a.-ethenoestra-l ,3,5(1 0)-trien-16-one, with the 15-ketone as the major isomer. Treatment of these ketones with LSelectride® afforded 3-methoxy-14, 17a.-ethenoestra-l ,3,5(10)-trien-15P-ol and 3- methoxy-14, 17 a.-ethenoestra-1,3 ,5(1 0)-trien-16P-oL Standard deprotection afforded the corresponding diols which were submitted for biological evaluation. An approach towards the corresponding a-alcohols which was investigated is based upon the Baeyer-Villiger oxidation of 16a.-acetyl-3-methoxy-l 4, 17a.-ethenoestra1,3,5(10)-triene. This compound was obtained as the minor product of the boron trifluoride mediated reaction between the 14, 16-diene and methyl vinyl ketone (MVK). The major compound was formulated 16a.-acetyl-3-methoxy-17P-3'- oxobutyl-14, l 7a.-ethenoestra-1,3,5(10)-triene, on the basis of the available spectral data. Reaction of MVK and the 14,16-diene under thermal conditions afforded the desired 16a.-acetyl compound as the major product. Attempts to perform the peracid mediated insertion ofoxygen were unsuccessful. The final phase of the work w